The Influence of Profitability, Leverage, and Good Corporate Governance on the Value of Government Banking Companies 2020–2023 Period - Lisa Karena Putri; Lalu Hamdani Husnan (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The Indonesian state-owned banking sector faces valuation challenges post-COVID-19 pandemic despite fundamental improvements. This study aims to analyze the effect of profitability (ROA), leverage (DER), and Good Corporate Governance (GCG) on the firm value (PBV) of state-owned banks (Himbara) for the 2020-2023 period. Using a quantitative associative-causal approach, the population includes five Himbara banks with a census sample of 20 firm-year observations through purposive sampling. Secondary data from financial statements were analyzed using SPSS multiple linear regression after classical assumption testing. The results show that the three variables have no significant effect, either partially (sig. >0.05) or simultaneously (Sig. F=0.508; R²=13.1%). The conclusion states that external factors dominate the valuation of state-owned banks, suggesting a focus on policy transparency.